Law and crime / by Gery Johnstone and Tony Ward - "Johnstone, Gerry" (Los Angeles, 2010)
Law & Crime guides readers through the complex legal, philosophical and criminological debates that shape our understanding of crime, criminal justice and criminal responsibility. The book Introduces key topics, including: The development of criminal law institutions Criminalization, Fault and criminal responsibility, Corporate crime and crimes of the powerful The criminal trial Punishment. How criminal law is applied in cases of genocide, mass violence, torture and other violations of human rights. Aimed at students with no prior knowledge of law, the book includes many useful features to enhance understanding, from chapter overviews and key terms to study questions and suggestions for further reading. It is essential reading for students and academics in criminology, criminal justice and law.
Keywords: "Criminal justice, Administration of"